APLIKASI REGRESI LOGISTIK DALAM ANALISIS FAKTOR RISIKO ANEMIA GIZI PADA MAHASISWA BARU IPB - Indah Irma Maharani; Hardinsyah Hardinsyah; Bambang Sumantri (Food and Nutrition Society of Indonesia, 2007)
This study was aimed at analyzing risk factors of nutritional anemia among new students of Bogor Agricultural University (IPB). A logistic regression model for 1907 new students’ record data matched with health record data was selected and applied on anemia risk factors analysis. The result showed that 10.9% and 21.4% of the students were suffering from nutritional anemia and proteinuria respectively. The risk factors of nutritional anemia among the new students of IPB are sex, age, family income and proteinuria status. The nutritional anemia risk is higher among female students (OR = 1.36); among younger age (age < 18 year); among students from low income family (OR = 1.70); and students suffered from proteinuria (OR = 1.49). This implies that the regular monitoring and controlling of both anemia and proteinuria among the students by Polyclinic of IPB are urgently required.